Antimicrobial Susceptibility and Molecular Epidemiology of Multidrug-resistant Pseudomonas aeruginosa in Northeast of Brazil - , Stephanie de Almeida-Alves; , Ludimila Gomes Pinheiro; , Izabelly Linhares Ponte-Brito; , Paulo de Tarso Teles Dourado de Aragão; , Guilherme Mendes Prado; , Júlio César Sousa Prado; , Raquel Oliveira dos Santos Fontenelle; , Francisco Cesar Barroso Barbosa (Archives of Current Research International, 2024)
Introduction: This study aimed to investigate the antimicrobial susceptibility profile of nosocomial strains of Pseudomonas aeruginosa isolated from inpatients of a teaching hospital in the City of Sobral, Ceará, in Northeast of Brazil (Santa Casa de Misericórdia de Sobral - SCMS) from March/2019 to March/2020, as well as to assess the occurrence of resistance genes bla-TEM, bla-SHV, bla-CTX-M 1/2, bla-IMP-1, bla-KPC, bla-GES, bla-SPM-1, bla- NDM-1, bla-VIM. Methodology: Bacterial identification and antimicrobial susceptibility tests (AST) were performed using the automated system Vitek®2. Conventional polymerase chain reaction (PCR) was used to amplify genes of interest. Results: Thirty-eight specimens of P. aeruginosa were collected. More than half of the isolates were resistant to imipenem (55.2%), and showed different rates of resistance to the other antimicrobials tested. In addition, intermediate susceptibility was also observed to gentamicin (7.8% of the isolates) and meropenem (10.52% of the isolates). The gene bla-CTX-M 1/2 was the most prevalent (41.9%), while bla-GES was highly identified among the carbapenemase-producing strains (12.9%). Conclusion: The results demonstrated considerable resistance rates to β-lactam antibiotics, which could be attributable to the indiscriminate use of these antibiotics in the analyzed hospital, whose control relies on the improvement of antimicrobial prescription policies.